Pemberdayaan Karang Taruna Desa dalam Pengembangan dan Pengelolaan Wisata Alam - Khoirul Afandi; Fuad Fitriawan; Jauhan Budiwan (Social Science Academic, 2025)
This program aims to improve the quality of community empowerment in the Development and Management of Tourism Villages in Sukorejo Village, Sukorejo District, Ponorogo Regency, East Java Province. One of the strategies implemented is to optimize the human resources of youth organizations to be more astute in exploiting local tourism potential. The main target of this activity is Karang Taruna Bolo Sewu and all elements of society in Sukorejo Village. Apart from that, students also collaborate with the village government by holding digital seminars aimed at promoting local tourism through digital media. The Bolosewu Youth Organization's activity method in Sukorejo Village in the KPM program with the theme "Powerful Villages with Local Potential" uses qualitative methods by gathering information from local community leaders. The program or solution offered is 1) Increasing the human resource capacity of the Village Youth Organization through discussions whose contents emphasize village empowerment with local potential. 2) Developing Village Potential through the learning process and seminar training. In order to create a community that is aware of the potential of the Sukorejo village tourism village, the activity implementers involve village youth groups, field supervisors (DPL), students, and the village government as partners in implementing KPM activities. From several programs implemented, the sustainability of the program can be seen from the realization of the activities that will later be carried out by the youth organization and the local community.